2021
DOI: 10.1063/5.0056870
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the directional control of electron density and gas temperature in atmospheric pressure dielectric barrier discharge by using low- and high-frequency coupling modulation

Abstract: Dielectric barrier discharges (DBDs) are commonly used as efficient sources of large volume diffuse plasmas with moderate temperature and plenty of reactive particles, but the synergistic linkage of some key plasma parameters in single frequency driven systems sometimes limits their application fields and accessible operating ranges. The discrete control of certain key plasma parameters by multi-frequency, i.e., dual frequency (DF), voltage waveform excitations is of increasing requirement and importance for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…BOLSIG+ is a computer program that is widely used to numerically solve the Boltzmann equation for electrons in various types of gas discharges and collisional low-temperature plasmas. [46][47][48][49] By setting parameters such as gas components, collision cross-section and measured reduced electric field, the program can directly output the results of the electron energy distribution function, which allows to calculate the corresponding mean electron energy according to eqn (4), where e denotes the mean electron energy, f 0 denotes the EEDF, and e is the electron energy.…”
Section: Reduced Electric Field and Electron Energy Measurementmentioning
confidence: 99%
“…BOLSIG+ is a computer program that is widely used to numerically solve the Boltzmann equation for electrons in various types of gas discharges and collisional low-temperature plasmas. [46][47][48][49] By setting parameters such as gas components, collision cross-section and measured reduced electric field, the program can directly output the results of the electron energy distribution function, which allows to calculate the corresponding mean electron energy according to eqn (4), where e denotes the mean electron energy, f 0 denotes the EEDF, and e is the electron energy.…”
Section: Reduced Electric Field and Electron Energy Measurementmentioning
confidence: 99%
“…The dielectric barrier discharge (DBD) plasma generator, on the other hand, is relatively thin and generates less heat during plasma generation compared to inductively coupled plasma (ICP) [ 18 , 19 , 20 , 21 ]. However, the DBD plasma generator structure also requires the application of a high bias voltage, which generates significant heat that, although small compared to ICP, can cause structural deformation depending on the thermal tolerance of the DBD plasma generator components.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a dualfrequency source could efficiently enhance the plasma characteristics of an atmosphericpressure dielectric barrier discharge and provided a possible approach to controlling and optimizing key plasma parameters and even enabled separate control of density and gas temperature. They also performed numerical studies on the directional control of electron density and gas temperature in the dielectric barrier discharge using dual frequencies [10]. D. B. Kim et al [11] conducted experimental studies on the atmospheric pressure discharge plasma driven by a dual-frequency source combining radio frequencies of 2 and 13.56 Mhz.…”
Section: Introductionmentioning
confidence: 99%